Crimea-Tatars gathered on the birthday of Lenin to plead for return to the Crimea and restoration of the autonomous republic are dispersed by water canons
Crimea-Tatars gathered on the birthday of Lenin to plead for return to the Crimea and restoration of the autonomous republic are dispersed by water canons.